Daily lives of residents with dementia in nursing homes: development of the Maastricht electronic daily life observation tool. (23rd March 2016) - de Boer, B.; Beerens, H.C.; Zwakhalen, S.M.G.; Tan, F.E.S.; Hamers, J.P.H.; Verbeek, H.
ABSTRACT: Background: Daily life is a dynamic and multidimensional concept, for which appropriate assessment tools are lacking. This study describes the development of the Maastricht Electronic Daily Life Observation tool (MEDLO-tool), a freely accessible, easy to use, electronic observation tool to assess relevant daily life aspects for nursing home residents with dementia. Methods: (1) Determining relevant aspects of daily life for nursing home residents with dementia based on a literature search and expert interviews; (2) pilot testing observation procedures and operationalizations of the aspects of daily life; and (3) exploring inter-rater reliability and feasibility of the tool in a nursing home facility with 16 residents (56% female, mean age: 77). Results: The following aspects of daily life are assessed with the MEDLO-tool: (1) activity (activity performed by resident, engagement in this activity, and the degree of physical effort); (2) physical environment (location of the resident and interaction with the physical environment); (3) social interaction (the level and type of social interaction, and with whom this social interaction took place); and (4) emotional well-being (mood and agitation). Each aspect of daily life is observed and scored using standardized scoring options. Agreement on the aspects is high with an average absolute agreement of 86%. Users of the MEDLO-tool indicated that it was feasible in practice and contained clear operationalization of the aspects of daily life. Conclusions: The MEDLO-tool is a promising tool to gain real time insight into the aspects of the daily lives of nursing home residents with dementia.